Mouse models of sarcopenia: classification and evaluation. Issue 3 (5th May 2021) - Xie, Wen‐qing; He, Miao; Yu, Deng‐jie; Wu, Yu‐xiang; Wang, Xiu‐hua; Lv, Shan; Xiao, Wen‐feng; Li, Yu‐sheng
Abstract: Sarcopenia is a progressive and widespread skeletal muscle disease that is related to an increased possibility of adverse consequences such as falls, fractures, physical disabilities and death, and its risk increases with age. With the deepening of the understanding of sarcopenia, the disease has become a major clinical disease of the elderly and a key challenge of healthy ageing. However, the exact molecular mechanism of this disease is still unclear, and the selection of treatment strategies and the evaluation of its effect are not the same. Most importantly, the early symptoms of this disease are not obvious and are easy to ignore. In addition, the clinical manifestations of each patient are not exactly the same, which makes it difficult to effectively study the progression of sarcopenia. Therefore, it is necessary to develop and use animal models to understand the pathophysiology of sarcopenia and develop therapeutic strategies. This paper reviews the mouse models that can be used in the study of sarcopenia, including ageing models, genetically engineered models, hindlimb suspension models, chemical induction models, denervation models, and immobilization models; analyses their advantages and disadvantages and application scope; and finally summarizes the evaluation of sarcopenia in mouse models.